SITE INDEX PREDICTION OF SMALLHOLDER PLANTATIONS OF KAYU BAWANG (Disoxylum mollissimum Blume) IN BENGKULU PROVINCE - Siahaan, Hengki; Sumadi, Agus (Indonesian Journal of Forestry Research, 2015)
Kayu bawang (Dysoxylum mollissimum Blume) has been planted almost in all districts of Bengkulu Province, Indonesia, but few studies have been conducted to estimate the site quality of this species. This study aimed to asses site quality ofÂ  Â Dysoxylum mollissimum Blume on smallholder plantation by establishing 32 permanent sample plots (PSPs) distributed in six districts of Bengkulu Province and measured periodically from 2006 to 2012. The result shown that the robust model for dominant height growth of Dysoxylum mollissimum Blume in Bengkulu Propince was Schumacher model expressed by the equation: Ln Ho = (3,06322 + ai) â 2,04777/A (R2 = 96,5%, AMRES = 0,82 and APD =5,03%).Â  Site equation for this species based on the dominant height growth model wasÂ  Ln Si = Ln H0 â 2,04777 (1/12-1/A) for age index of 12 years. Based on this equation, the site were classified into five classes having an equal range of 3 metres, includes SI < 16 m; 16 m â¤ SI < 19 m; 19 m â¤ SI <Â  22 m; 22 m â¤ SI < 25 m; and SI â¥ 25 m for site class I, II, III, IV, and V representing from the most poor to the highest productivity respectively. Good site quality was mostly found in lowland having altitude < 300 m above sea level and bulk density > 0,9 g/cc.